2000
DOI: 10.1074/jbc.m004304200
|View full text |Cite
|
Sign up to set email alerts
|

Cap-Poly(A) Synergy in Mammalian Cell-free Extracts

Abstract: The 5 cap and 3 poly(A) tail of eukaryotic mRNAs cooperate to stimulate synergistically translation initiation in vivo, a phenomenon observed to date in vitro only in translation systems containing endogenous competitor mRNAs. Here we describe nuclease-treated rabbit reticulocyte lysates and HeLa cell cytoplasmic extracts that reproduce cap-poly(A) synergy in the absence of such competitor RNAs. Extracts were rendered poly(A)-dependent by ultracentrifugation to partially deplete them of ribosomes and associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
57
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(60 citation statements)
references
References 33 publications
3
57
0
Order By: Relevance
“…Recent data have shown that another mechanism related to in vivo translational initiation, the interaction between the cap and poly(A) tail of eukaryotic mRNAs, does not occur in Flexi rabbit reticulocyte lysates. Instead, the mechanism operates in a modified system based on ribosome-depleted rabbit reticulocyte lysates (29,30). Alternatively, the translation of the ARFP/F/coreϩ1 protein may be regulated by different mechanisms depending on the cellular conditions and the ways in which the translation machinery is modified during HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have shown that another mechanism related to in vivo translational initiation, the interaction between the cap and poly(A) tail of eukaryotic mRNAs, does not occur in Flexi rabbit reticulocyte lysates. Instead, the mechanism operates in a modified system based on ribosome-depleted rabbit reticulocyte lysates (29,30). Alternatively, the translation of the ARFP/F/coreϩ1 protein may be regulated by different mechanisms depending on the cellular conditions and the ways in which the translation machinery is modified during HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Because a competitive environment is assured by rendering translation components physically limiting, rather than by adding excess competitor mRNAs, this system allows the molecular dissection of the functional interactions between mRNA 5Ј and 3Ј ends (17,19,22). Here we describe the use of this system for a detailed study of the effect of exogenous poly(A) on translation of mRNAs carrying various combinations of 5Ј cap and 3Ј poly(A) tail.…”
mentioning
confidence: 99%
“…The recent demonstrations that plant, yeast, and mammalian PABP can interact physically with the N-terminal part of eIF4G (11)(12)(13) and that capped polyadenylated mRNAs can be physically circularized in vitro by the addition of purified eIF4E, eIF4G and PABP (14) suggest that cap-poly(A) cooperativity somehow results from the physical interactions between the mRNA 5Ј and 3Ј ends (9,15). Indeed, disruption of the eIF4G-PABP interaction abolishes both the positive effects of poly(A) on uncapped mRNA translation in yeast (16) and abrogates cap-poly(A) synergy in cellfree mammalian extracts (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a mechanism was demonstrated in yeast, plant, and mammalian systems (2,3) and plays a key role during development of Xenopus, Drosophila, and mouse (4). Translational synergy was also recapitulated in vitro (5)(6)(7)(8)(9). Hence, the cap-poly(A) tail synergy represents a common paradigm for translational control.…”
mentioning
confidence: 83%